Hubungan Antara Tingkat Kepercayaan Diri Dengan Prestasi Belajar Pendidikan Jasmani - Gumilar Mulya; Resty Agustryani (Gladi : Jurnal Ilmu Keolahragaan, 2020)
This study aims to examine the level of confidence relationship with physical education learning achievement in elementary schools in the Tawang sub-district, Tasikmalaya City. The research method uses descriptive-correlational. The sample in this study is the sixth-grade students selected representing several schools in the District of Tawang as many as 60 students employing a purposive sampling technique. The instrument used was a confidential questionnaire. Data processing procedures to obtain answers about whether or not the hypothesis is accepted following the proposed significance are: (1) looking for averages, (2) looking for standard deviations, (3) testing normality through the Lillefors test (4) testing the correlation of two variables. Based on the results of research and statistical calculations on hypothesis testing the relationship of the level of confidence with physical education learning achievement, the authors can conclude as follows; there is a significant relationship between self-confidence and student achievement in class VI in Tawang District, Tasikmalaya City. Because the significance value obtained is greater than 0.05, and the value of Yxy (0.90)> (0.250) rtable (0.05) (60) then H0 is rejected and Ha is accepted, so there is a significant relationship between self-confidence and achievement learning (significant).